The portal - Lasky, Kathryn; OverDrive, Inc. (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2019)
"Life used to be great for Rose: full of friends, a loving mom, and a growing fashion blog. But when her mother dies in a car crash, Rose is sent away to live with a strange grandmother she hardly knows and forced to attend a new school where mean girls ridicule her at every turn. The one place Rose finds refuge is in her grandmother's Tudor-style greenhouse. But one night, she sees a strange light glowing from within it. She climbs a ladder to investigate... and finds herself transported back four hundred years to Hatfield Palace, where she becomes servant and confidante of the banished princess Elizabeth, daughter of King Henry VIII. Rose soon discovers something else surprising -- a locket with two mysterious images inside it, both of them clues to her own past. Could her grandmother's greenhouse portal offer answers to the mysteries of her family... and their secrets? And how will she ever unravel them all?" --.
Electronic book.
Ages 8-12.
Electronic reproduction.
Keywords: Elizabeth -- I, -- Queen of England, -- 1533-1603 -- Juvenile fiction; Elizabeth -- I, -- Queen of England, -- 1533-1603.; Time travel -- Juvenile fiction; Orphans -- Juvenile fiction; Family secrets -- Juvenile fiction; Grandmothers -- Juvenile fiction; Traffic accidents -- Juvenile fiction; Mothers -- Death -- Juvenile fiction; Time travel; Mothers -- Death; Advantage title -- Fiction; Family problems -- Fiction; Family secrets; Grandmothers; Mothers -- Death; Orphans; Time travel; Traffic accidents; JUVENILE FICTION / Science Fiction / Time Travel; Fiction; Juvenile works; Electronic books; Historical fiction; Science fiction